IMPROVING STUDENT'S VOCABULARY MASTERY BY USING OSTENSIVE MEANS (AN ACTION RESEARCH AT THE FIFTH YEAR OF SD NEGERI NGARGOTIRTO I IN 2009/2010 ACADEMIC YEAR) - PERMANA, TAUFAN (2011)
The objectives of this study are to describe the problems faced by the teacher in teaching vocabulary to the students and to know the improvement of student in mastery vocabulary by using ostensive means in the fifth year students of SD Negeri Ngargotirto 1, Academic Year 2009/2010. The students have problems dealing with vocabulary, first, they had difficulty to remember the meaning of word, second they have bad pronunciation, and third, they are not interested in English lesson. The researcher designed an action research using ostensive means to teach vocabulary. The research was done on February until April 2010 and took 40 students as the object. The researcher got the data from events, informants, document, and tests. While the techniques of collecting data were observation, interview, and documentation. The action research was conducted in two cycles. To find the significant improvement of the students' vocabulary mastery, the researcher conducted tests. The tests were pre-test and post tests. The researcher analyzed the mean scores of the tests. To analyze the significant differences between pre-test and post-test, the researcher used the non-independent t-test computation. The result of the research showed that ostensive means could solve the problems occurring teaching vocabulary and improve the students' vocabulary mastery. Using ostensive means, the students showed great interest to be actively involved in the teaching learning process. In the classroom, they were eager to join all activities and practice pronunciation. Some students could pronounce words correctly. The students could not only grasp the meaning of the vocabulary at the moment the words taught but they could also remember the vocabularies at the following meeting. Meanwhile, to find the significant difference between the students' achievement before and after action, he used the non-independent t-test. The result showed that the t-observation is always greater than the t-table in degrees of freedom N-1 and level of significance 0,05. It showed that there was a significant improvement of the students' vocabulary mastery before and after the research. The conclusion is the teaching vocabulary using Ostensive Means in The fifth year students of SD Negeri Ngargotirto 1 yields a good result.